2010
DOI: 10.1007/s10549-010-1066-x
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter phase II randomized trial evaluating antiangiogenic therapy with sunitinib as consolidation after objective response to taxane chemotherapy in women with HER2-negative metastatic breast cancer

Abstract: The aim of this study is to test the hypothesis that antiangiogenic treatment with sunitinib consolidation can prolong remissions induced by taxane-based chemotherapy in women with metastatic breast cancer. The method involves a two-arm open-label (2:1 randomization) multicenter, randomized phase II trial evaluating the efficacy of sunitinib (arm A) versus no therapy (arm B) in patients with HER-2-negative metastatic breast cancer who achieved an objective response to taxane-based chemotherapy. The results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 22 publications
0
14
0
4
Order By: Relevance
“…The highest occurrence (30.8%; 95% CI, 26.7-35.0%) was seen in a Phase III trial for ovarian cancer [69], whereas the lowest overall incidence was detected in ten trials that reported no sign of high-grade hypertensive events [27, 33, 36, 46, 56, 62, 63, 75, 78, 85]. A random-effects model (c 2 -based Q-statistic test: q = 1065.86; P < 0.001; I 2 = 93.4%) revealed that the total occurrence of all-grade hypertensive occasions in cancer patients treated with VEGFR-TKIs was 4.4% (3.7-5.0%, 95% CI, Supplementary Table 4 and Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…The highest occurrence (30.8%; 95% CI, 26.7-35.0%) was seen in a Phase III trial for ovarian cancer [69], whereas the lowest overall incidence was detected in ten trials that reported no sign of high-grade hypertensive events [27, 33, 36, 46, 56, 62, 63, 75, 78, 85]. A random-effects model (c 2 -based Q-statistic test: q = 1065.86; P < 0.001; I 2 = 93.4%) revealed that the total occurrence of all-grade hypertensive occasions in cancer patients treated with VEGFR-TKIs was 4.4% (3.7-5.0%, 95% CI, Supplementary Table 4 and Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…Trastuzumab has been shown to induce tumor regression in such patients. Sunitinib, sorafenib, and bevacizumab are multitargeted tyrosine kinase inhibitors that inhibit tumor neovascularization and are currently in clinical trials [2, 3]. These drugs are associated with serious problems such as adverse effects, drug resistance, and low efficacy of single therapy, particularly against metastatic or recurrent breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In 2010, a multicenter Phase II trial was conducted to evaluate whether sunitinib consolidation could prolong remission after taxane-based chemotherapy in HER-2 negative metastatic breast cancer (MBC) (29). Only 28% of patients achieved the 5-month PFS endpoint after starting sunitinib and due to higher rates of toxicity (69% of Grade 3/4 toxicity), the study failed to confirm the hypothesis.…”
Section: Antiangiogenic Treatment Efficacymentioning
confidence: 99%